Pengaruh Latihan High Intensity Interval Training (HIIT) terhadap PeningkatanVO2MAX pada Atlet Bulutangkis PB Tunas Jaya Kasturi Kota Jambi - Maharani; Sukendro; Yanto, Anggel Hardi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This research aims to determine the effect of High Intensity Interval Training (HIIT) on improving VO2Max results in badminton athletes at PB Tunas Jaya Kasturi Jambi City. Badminton is a physically demanding sport that requires strength, endurance, muscle power, agility, speed and accuracy. The study used a one group Pretest-Posttest design, where measurements were taken before and after treatment to obtain more accurate results. Hypothesis testing using t-test showed t-value of 11.087 > 2.145 (t-table) with a significance probability value of 0.000 < 0.05, thus Ha was accepted. This proves that there is a significant effect of HIIT on improving VO2Max results in badminton athletes. Based on the mean difference, the results show that HIIT was able to provide a VO2Max improvement of 45.26% compared to before training. This research provides empirical evidence that HIIT programs are effective for improving aerobic capacity of badminton athletes and can be considered as a training method to enhance athlete performance.